PENGARUH GAYA KEPEMIMPINAN SERTA LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI SEKRETARIAT DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING STUDI PADA KANTOR SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN AGAM (LUBUK BASUNG) - Puji, Ayu Fransisca; Neldi, Mondra; Charly, Chintya Ones (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This study aims to determine the influence of Leadership Style and Work Environment on Employee Work Productivity with Work Motivation as an Intervening Variable. The population of this study was employees of the Secretariat of the Regional People's Representative Council of Agam Regency. The sampling technique in this study used the Census Method with a sample of 58 employees. Data collection techniques through questionnaires that have been tested for validity and reliability. The data analysis technique in this study uses the SmartPLS 3 Structural Equation Modeling (SEM) method. The results showed that Leadership Style has a positive and significant effect on Work Motivation, Work Environment has a positive and significant effect on Work Motivation, Leadership Style has a positive and insignificant effect on Employee Work Productivity, Work Environment has a positive and insignificant effect on Employee Work Productivity, Work Motivation has a positive and significant effect on Employee Work Productivity, Leadership Style has a positive and significant effect on Employee Work Productivity through Work Motivation, Work Environment has a positive and significant effect on Employee Work Productivity through Work Motivation, the contribution of Leadership Style and Work Environment of 74.2% to Work Motivation, and the contribution of Leadership Style, Work Environment and Work Motivation of 79.9% to Employee Work Productivity.